Evaluation of pH in swine carcasses regarding on the trasport distance of the animals: a case study (Research, Society and Development, 2020)
The PSE (Pale, Soft and Exudative) swine meat is an anomaly that produces great economic losses in the swine industry and products because proteins lose their functionality, affecting the ability of water retention, binding, and emulsification of meat. Due to the importance of quality control of carcasses, the determination of the pH parameter is necessary to perform the classification of the product in: normal; PSE; and DFD (Dark, Firm, and Dry). In this sense, the purpose of the work was to perform the evaluation of pH values after 45 minutes of bleeding (pH45) and function of the distance from farms to a slaughterhouse and calculate the indicator of Meat PSE in swine carcasses. The experiment was carried out in a large plant, under the supervision of the Federal Inspection Service (SIF). A total of 725 carcasses were used, separated into lots and the transport distance from the farms to the slaughterhouse ranged from 25 to 427 km. For the evaluation of the incidence of PSE, pH45 was measured by a direct method, and the management of pre-slaughter animals was standardized for all lots, except for rest time. The animals transported for shorter distances (25 and 65 km) presented 11% indicative of PSE meat, a fact that shows that the stress response is higher when the animals are subjected to short transport distances compared to longer distances (320, 340, and 427 km).